Atividade antifúngica do geraniol sobre leveduras multirresistentes do gênero candida e perfil farmacológico e toxicológico em estudos in silico - Pereira, Julio Abrantes (2017)
Currently, throughout the globe, there has been an increase in the frequency of cases of candidiasis, an opportunistic infection commonly treated with fluconazole. With the indiscriminate use of this and other antifungals cases of candidiasis by multiresistant strains have emerged, making it necessary to search for new drugs. Several natural products such as monoterpene geraniol have demonstrated antimicrobial activity to various microorganisms. The present study aimed to evaluate the antifungal activity of geraniol against strains of Candida albicans, C. glabrata and C. krusei resistant to fluconazole by means of microdilution techniques, evaluating the minimum inhibitory concentration - CIM, minimum fungicidal concentration - CFM, cell wall effect (sorbitol assay), binding to membrane ergosterol, effect of association of this monoterpene with fluconazole and amphotericin B antifungal agents by the checkeboard technique and modulation assay. Pharmacological, toxicological and possible spectra of geraniol activity were also verified by in silico assays using the Osiris, Molinspiration and Pass online software. The analysis showed that geraniol showed excellent antifungal activity against all multiresistant strains with a 512μg/mL CIM90, and a fungicidal effect dependent concentration after 8 hours of exposure with the CFM90 of 512μg/mL. Fungal wall and did not interact with the ergosterol of the cell membrane, nor did it show a synergistic, antagonistic or modulating effect of this phytoconstituent on fluconazole and amphotericin B. The in silico tests showed that geraniol has a good theoretical oral bioavailability, as well as numerous Although it presents the risk of an irritant effect, it does not present mutagenic, tumorigenic or reproductive effects, which leads to the conclusion that geraniol is a good candidate in the fight against multidrug resistant strains of Candida.